Desain Aplikasi Akuntansi pada LAZISMU Lamongan - Isnaini Hidayatun Muharromah; Nur Fatoni; Dessy Noor Farida (Jurnal Akuntansi Indonesia, 2021)
This writing aims to design an information system that produces applications regarding accounting on zakat contained in amil zakat institutions, infaq and shadaqah Muhammadiyah Lamongan. Before the design is designed properly, it is necessary to analyze the financial recording system contained in LAZISMU Lamongan. The results of the analysis of the accounting application system used by LAZISMU Lamongan will be taken into consideration for the process of designing an accounting application system design. The method that can be used to design this system design is the System Development Life Cycle (SDLC) methodology. Where this method has a function as a helper to analyze, accelerate and can produce accuracy to present a solution and provide a sequential or sequential approach to the software life flow starting from the analysis, design, coding, testing and support stages. The form of design that will be applied to the Amil Zakat Institute for Infak and Shadaqah Lamongan is in the form of automation designed using Microsoft Excel combined with Visual Basic for Applications. In the design of the application design contains sheets where regarding the application of the accounting cycle starting from recording a list of accounts and account codes, classifying accounts, recording transactions in general journals then ledgers to several financial reports which include; statement of financial position, changes in funds, changes in assets under management, cash flow and a list of fixed assets (Statement of Financial Accounting Standards No. 109 concerning zakat).Keywords: Accounting Applications, General Ledger Excel, Visual Basic for Application, PSAK No 109.ABSTRAKPenulisan ini memiliki tujuan untuk mendesain sistem informasi yang menghasilkan aplikasi mengenai akuntansi pada zakat yang terdapat di lembaga amil zakat, infaq dan shadaqah muhammadiyah Lamongan. Sebelum desain dirancang secaa baik perlu melakukan analisis sitem pencatatan keuangan yang terdapat pada LAZISMU Lamongan. Hasil analisis dari sistem aplikasi akuntansi yang digunakan oleh LAZISMU Lamongan akan dijadikan pertimbangan untuk melakukan proses perancangan desain sistem aplikasi akuntansi. Adapun metode yang bisa digunakan untuk merancang desain sistem ini adalah metodologi System Development Life Cycle (SDLC). Dimana metode ini memiliki fungsi sebagai pembantu menganalisa, mempercepat dan bisa menghasilkan ketepatan untuk memaparkan sebuah solusi dan menyediakan pendekatan alur hidup perangkat lunak secara sekuensial atau urut mulai dari analisis, desain, pengkodean, pengujian dan tahap support. Bentuk desain yang akan diterapkan pada Lembaga Amil Zakat Infak dan Shadaqah Lamongan berupa otomatisasi yang dirancang menggunakan Microsoft excel dipadukan dengan Visual Basic for Application. Didalam perancangan desain aplikasi tersebut berisi sheet-sheet dimana mengenai pengaplikasian siklus akuntansi yang dimulai dari pencatatan daftar akun dan kode akun, penggolongan akun-akun, pencatatan transaksi pada jurnal umum kemudian buku besar sampai beberapa laporan keuangan yang meliputi; laporan posisi keuangan, perubahan dana, perubahan asset kelolaan, arus kas dan daftar aset tetap (Pernyataan Standar Akuntnasi Keuangan No 109 tentang zakat).Kata Kunci: Aplikasi Akuntansi, General Ledger Excel, Visual Basic for Aplication, PSAK No 109.